An active common‐noise canceler combined with feedback control. Issue 2 (29th May 2021) - Ohara, Shunsuke; Ogasawara, Satoshi; Takemoto, Masatsugu; Orikawa, Koji; Yamamoto, Yushin
Abstract: This paper describes the methods for improving the performance of an active common‐noise canceler (ACC) that suppresses the common‐mode (CM) voltage generated by inverters. Whereas the already proposed ACC (ACC0) compatible with space vector pulse width modulation requires two emitter follower circuits, this paper proposes an improved ACC (ACC1) that requires a single emitter follower. In addition, an ACC (ACC2) that improves the CM voltage suppression performance by adding a feedback circuit to ACC1 is also proposed. The experimental results show that ACC1 improved the CM voltage attenuation by −10 dB compared to ACC0, and ACC2 improved the CM voltage attenuation by −20 dB compared to ACC1. ACC2 has a large CM voltage attenuation of up to −53 dB in the wide frequency range from 100 kHz to 5 MHz.